The Concept of Fana and Its Relevance deep Prevention of Religious Radicalism - Muhammad Saleh Cahyadi Mohan (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2023)
This study examines the concept of mortality from the perspective of Imam Junaid Al-Baghdadi and its relevance in counteracting religious radicalism. This research is library research using primary data from the book of Rasail Junaid and using descriptive-analytical techniques in analyzing the data. This research found that there are three levels of mortality in the view of Imam Junaid Al-Baghdadi; first, mortal towards morals through persistence against lust and consistently avoiding actions that violate norms, second, mortal in worship by not being transactional when worshiping Allah, third, mortal towards self, so that Allah dominates in him, thus it can be concluded that if a person succeeds in reaching these three mortal levels, then he will give birth to goodness in his behavior, sincerity in his life, and always feel supervised by God in all aspects of his life. So that through the understanding and experience of the three mortal levels, religion is not used as a source of violence, but religion is a source of goodness and sincerity. This research is expected to be able to add to scientific treasures about the thoughts of Imam Junaid Al-Baghdadi and to contribute knowledge in preventing religious radicalism in Indonesia